2007
DOI: 10.1007/s10495-007-0092-6
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor rescues trophoblast apoptosis induced by reactive oxygen species

Abstract: Pre-eclampsia and intrauterine growth restriction are associated with increased apoptosis of placental villous trophoblast. This may result from placental hypoperfusion, leading to the generation of reactive oxygen species (ROS). Apoptosis can be induced in villous trophoblast following exposure to oxidative stress. Epidermal growth factor (EGF) reduces trophoblast apoptosis resulting from exposure to hypoxia. We hypothesised that exposure to hydrogen peroxide, a potent generator of ROS, would induce apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 56 publications
8
48
2
Order By: Relevance
“…The protocol was followed according to the manufacturer's instructions with minor modifications, as previously reported. 25 Negative controls involved application of labeled-dUTP to sections in the absence of TdT enzyme.…”
Section: Detection Of Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…The protocol was followed according to the manufacturer's instructions with minor modifications, as previously reported. 25 Negative controls involved application of labeled-dUTP to sections in the absence of TdT enzyme.…”
Section: Detection Of Apoptosismentioning
confidence: 99%
“…To determine the extent of vascular remodeling, qualitative analysis was performed on 50 vessels selected randomly from the total 25 immunostained decidua basalis samples, to assess the degree of VSMC and endothelial cell disruption and loss, and the presence or absence of vEVTs. Vessels were classified into four different types, based on the combination of attributes and this was tested by three independent observers blind to the identity of the tissue.…”
Section: Analysis Of Vascular Remodelingmentioning
confidence: 99%
“…Trophoblast cells express ET precursors and receptors (163). Fiore et al (47) showed that exaggerated levels of ET-1 trigger placental villi to produce reactive oxygen species, which promote trophoblast apoptosis (47,116). Placentas from preeclamptic pregnancies have increased placental oxidative stress and ET-1 binding (8,22).…”
Section: Effects Of Obesity On the Placental Function And Perfusionmentioning
confidence: 99%
“…Recently, several studies have suggested that soluble factors in the maternal circulation, including growth factors, can influence placental development and function (Baczyk et al 2005, Johnstone et al 2005b, Sferruzzi-Perri et al 2006, Moll et al 2007, Forbes et al 2008, 2010a,b,c, Hoffmann et al 2009). This review will examine the role of such growth factors in the regulation of trophoblast function by briefly discussing their effect on extravillous trophoblast invasion (see the recent review by Knofler (2010) for more detail on this topic), and focussing in detail on the control of villous cytotrophoblast proliferation and function.…”
Section: Placental Development and Fetal Growthmentioning
confidence: 99%
“…EGF promotes trophoblast proliferation and cell survival by stimulating PI3K/AKT pathway (Johnstone et al 2005a, Moll et al 2007, while in placental stromal cells, the PI3K/AKT pathway is required for FGF2 and vascular endothelial growth factor-stimulated endothelial cell proliferation (Wang et al 2009). It is now emerging that PI3K/AKT may also play additional roles within the placenta by regulating expression of leptin (Gambino et al 2010), a known mediator of trophoblast proliferation and survival (Magarinos et al 2007).…”
Section: Pi3k/akt Pathwaymentioning
confidence: 99%